Ride, Fly Guy, ride! - Arnold, Tedd (New York : Cartwheel Books, 2012)
While riding in the car with Buzz and his father, Fly Guy gets blown out of the window and finds himself riding in a truck, then a boat, a train, an airplane, and maybe even a rocket.
Keywords: Flies -- Fiction; Transportation -- Fiction; Flies -- Fiction; Transportation -- Fiction